NICKEL-HYDROGEN COLD FUSION BY INTERMEDIATE RYDBERG STATE OF HYDROGEN: SELECTION OF THE ISOTOPES FOR ENERGY OPTIMIZATION AND RADIOACTIVE WASTE MINIMIZATION: NICKEL-HYDROGEN COLD FUSION BY INTERMEDIATE RYDBERG STATE OF HYDROGEN: SELECTION OF THE ISOTOPES FOR ENERGY OPTIMIZATION AND RADIOACTIVE WASTE MINIMIZATION - Sargoytchev, Stoyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The main objection against cold fusion is based on the theoretical understanding that the Coulomb barrier of the very small nucleus is extremely strong. The size of the atomic nucleus is determined by scattering experiments in which a metal target is usually struck by alpha particles. These experiments yield only energy and angular resolution and their interpretation rely on the assumption that the atomic nuclei and all elementary particles are spherical. A non-spherical nucleus made of thinner non-spherical particles like a torus or a twisted or folded torus will provide similar data for a limited range of the particle energy. At the time of Rutherford, alpha particles with energy from 4 to 8 MeV were used. Modern scattering experiments with energy above 25 MeV show a sharp deviation from the Rutherford theory. They also show a wavelike shape of the scattering cross section as a function of scattering angle. A new interpretation of the scattering experiments leads to the idea that the Coulomb field near the nucleus has a manifold shape with a much larger overall size and therefore is not so strong. The BSM-SG models of atomic nuclei are in excellent agreement with this conclusion. Applying the approach described in the monograph Structural Physics of Nuclear Fusion with BSM-SG atomic models, the highly exothermal process between nickel and hydrogen is analyzed. It leads to the conclusion that a proton capture may occur at an accessible temperature in a range of a few hundred degrees. The process is assisted by an intermediate state of hydrogen, known as the Rydberg atom, the magnetic field of which interacts constructively with the recipient nucleus if it is in a proper nuclear spin state. The final conclusion is that it is theoretically possible to obtain nuclear energy without radioactive waste by proper isotope selection of involved elements.